Heterologous overexpression of Apocynum venetum flavonoids synthetase genes improves Arabidopsis thaliana salt tolerance by activating the IAA and JA biosynthesis pathways - Zhang, Mengchao; Lu, Xueli; Ren, Tingting; Marowa, Prince; Meng, Chen; Wang, Juying; Yang, Hui; Li, Chunhua; Zhang, Li; Xu, Zongchang (Frontiers in Plant Science, 2023)
Salt stress is a serious abiotic stress that primarily inhibits plant growth, resulting in severe yield losses. Our previous research found that flavonoids play important roles in A. venetum salt stress tolerance. In response to salt stress we noted that the flavonoid content was depleted in A. venetum. However, the detailed mechanism is still not clear. In this study, the expression patterns of three flavonoids synthetase genes, AvF3H, AvF3’H, and AvFLS were systemically analyzed under salt stress in A. venetum seedlings. The salt tolerance of transgenic Arabidopsis plants was improved by heterologous overexpression of these synthetase genes. The NBT and DAB staining results as well as H2O2 and O2•- content analysis revealed that under salt stress, ROS molecules were reduced in transgenic plants compared to WT plants, which corresponded to the activation of the antioxidant enzyme system and an increase in total flavonoid content, particularly rutin, eriodictyol, and naringerin in transgenic plants. External application of flavonoids reduced ROS damage in WT plants just like what we observed in the transgenic plants (without the external application). Additionally, our transcriptome analysis demonstrated that auxin and jasmonic acid biosynthesis genes, as well as signaling transduction genes, were primarily activated in transgenic plants under salt stress, leading to activation of the cell wall biosynthesis or modification genes that promote plant growth. As a result, we investigated the mechanism through flavonoids enhance the salt tolerance, offering a theoretical foundation for enhancing salt tolerance in plants.